Innovations and social media analytics in a digital society - Sousa, Maria José; Marques, Célio Gonçalo (CRC Press, 2021)
"The recent trends of digitalization of society is transforming the all the sectors of activity, namely, healthcare, education, tourism, Information technology, and others. Social media analytics are tools that can be used to measure the innovations and the relation with the companies with the citizens. This book focuses on state-of-the-art of social media analytics, and advanced innovation policies in the digitalization of the society. Nowadays, the number of applications that can be used to create and analyze social media analytics generates large amounts of data often called big data, including measures of the use of the technologies to develop or to use new services to improve the quality of life of the citizens"--